ChemInform Abstract: Catalytic, Enantioselective Sulfenylation of Ketone‐Derived Enoxysilanes. Issue 14 (April 2015) - Denmark, Scott E.; Rossi, Sergio; Webster, Matthew P.; Wang, Hao
Abstract: Three classes of Lewis bases, tertiary amines, sulfides, and selenophosphoramides, are identified as catalysts for the α‐sulfenylation of silyl enol ethers, but only chiral selenophosphoramides furnish α‐phenylthio ketones in good yields and enantioselectivities.